Analisis Faktor Yang Berkaitan Dengan Perubahan Berat Badan Maternal di Kabupaten Aceh Besar - Gani, Fitria Widya; Hermansyah, Hermansyah; Sulaiman, Sulaiman; Abdullah, Asnawi; Adamy, Aulina (Jurnal Ragam Pengabdian, 2026)
Maternal and infant mortality rates are born with high low birth weight determined by the nutritional status of expectant mothers. The prevalence of less energy is the risk of chronic female childbearing age 15–49 years pregnant at 17.3% in 2018. Changes in weight loss period become one of the things to be considered by the mother so that there is a risk reduction for the fetus that is conceived and in the process of birth. Dietary restrictions on the customs of the greater Aceh people cause expectant mothers to be difficult to meet the nutritional needs of mothers and infants. This research aims to analyze the culture related to maternal weight change in the Aceh Besar district. This research is descriptive-analytic by using a crossectional design. Research conducted in three Puskesmas of Aceh Besar (Ingin Jaya, Darul Imarah and Kuta Baro). The sample in this study was 122 respondents. Data analysis using univariate, bivariate, and multivariate analysis. The results showed that there was a maternal weight change relationship with the earned income (P=0.016) and the perception of obesity (P=0.019). Earned income was the dominant factor influencing maternal weight change (OR=4.94; P=0.007; 95% CI=1.56–15.68). It is hoped that the Aceh Health Office will improve the nutritional status of pregnant women and re-check K4 data.